Maturation changes the excitability and effective connectivity of the frontal lobe: A developmental TMS–EEG study. Issue 8 (15th January 2019) - Määttä, Sara; Säisänen, Laura; Kallioniemi, Elisa; Lakka, Timo A.; Lintu, Niina; Haapala, Eero A.; Koskenkorva, Päivi; Niskanen, Eini; Ferreri, Florinda; Könönen, Mervi
Abstract: The combination of transcranial magnetic stimulation with simultaneous electroencephalography (TMS–EEG) offers direct neurophysiological insight into excitability and connectivity within neural circuits. However, there have been few developmental TMS–EEG studies to date, and they all have focused on primary motor cortex stimulation. In the present study, we used navigated high‐density TMS–EEG to investigate the maturation of the superior frontal cortex (dorsal premotor cortex [PMd]), which is involved in a broad range of motor and cognitive functions known to develop with age. We demonstrated that reactivity to frontal cortex TMS decreases with development. We also showed that although frontal cortex TMS elicits an equally complex TEP waveform in all age groups, the statistically significant between‐group differences in the topography of the TMS‐evoked peaks and differences in current density maps suggest changes in effective connectivity of the right PMd with maturation. More generally, our results indicate that direct study of the brain's excitability and effective connectivity via TMS–EEG co‐registration can also be applied to pediatric populations outside the primary motor cortex, and may provide useful information for developmental studies and studies on developmental neuropsychiatric disorders.